The estimate multiple as a result of priori links accounting. Generalization of Cramer-Rao inequality - Kasianov, V. A.; Bojarsky, G. N. (Proceedings of National Aviation University, 1998)
It is shown, that the lowest Cramer-Rao bound for statistical estimation could be changed to accounting a priori links between estimated parameters and the residual variances could be essentially reduced. The case of two parameters being linked with algebraic linear equation to be estimated is considered. In the second part of the paper the results of “concordance” of flight information on the base of use of a centre motion and kinematics Euler relationships as a priori links are represented